CUTICULAR COMPONENT ANALYSIS FOR DISCRIMINATION OF Aedes Aegypti (DIPTERA: CULICIDAE) FROM SEVEN LOCALITIES IN SOUTH KALIMANTAN - Abdul Gafur (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2008)
Cuticular components of female Aedes aegypti from seven localities (populations) in South Kalimantan were compared. Mosquitoes from four populations of Banjarmasin, and one population each of Pelaihari, Barabai, and Kotabaru were sampled. Cuticular hydrocarbons were removed from adult female and were separated and quantified by gas chromatography. Stepwise discriminant analysis determined the degree of differences between populations. Using the concentration of the hydrocarbons in a linear discriminant function and the estimator obtained from cross validation, it was demostrated that specimens could be correctly allocated the population to which they belong with an average success rate of 80.6%. All (100%) specimens of populations outside Banjarmasin were correctly identified. There was reduced segregation of the four Banjarmasin populations, suggesting greater similarity in the hydrocarbons of Aedes aegypti from these populations. It was suggested that the greater similarity correlated with increased contact between populations in the region.